KOMPOSISI JENIS DAN PENGUASAAN EKOLOGI DI WILAYAH DESA PANGI KAWASAN CAGAR ALAM PANGI BINANGGA KABUPATEN PARIGI MOUTONG - Ernawati, Ernawati; Umar, Husain; Ramlah, Sitti (Jurnal Warta Rimba, 2013)
This research aimed to study the number of occupation of species composition in Pangi-Binangga Nature Reserve area. The research was conducted in Pangi-Binangga Nature Reserve area, village of Pangi, Parigi District, Parigi Motong Regency, Central Sulawesi, from April through Juni 2013. This study uses continous strip sampling method. Twenty plots (400m x 400m) were made in each line. The sampling intensity was 16 ha (5%) from the total 6000 ha of Pangi-Binangga Nature Reserve area. Hence vegetation date were analysed to determine the density, frequency, dominant, and Importance Value Index. The results showed that the highest Importance Value Index at tree level of vegetation was Pterospermum celebicum Miq. (25,08%), while at pole and sapling level, the highest IVI was Diospyros celebica Bakh with value 13,72% and 19,34%, respectively. Furthermore, the highest IVI at seedling level was Spathoglottis aurea (13,24%). Keywords : Species composition, Ecology occupation, Important Value Index, Pangi-Binangga Nature Reserve.